211k views
4 votes
Find the solution to the system of equations.

x + 4y - 5z = -6
x + 4y - 4z = -1
x + 5y - 4z = 3
A. x = 3, y = 4, z = 5
B. x = 5, y = 3, Z = 6
C. x = 3, y = 13, z = -14
O D. x = 4, y = 5, z = 3

User Molly
by
4.5k points

1 Answer

5 votes

Answer:

A.

Explanation:

first find value of x from eq.1 and 2

then value of y from equation 2 and 3

put these values in equation 1 to get value of x

Find the solution to the system of equations. x + 4y - 5z = -6 x + 4y - 4z = -1 x-example-1
User Quality Catalyst
by
5.0k points